2022
DOI: 10.1111/adb.13236
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in cocaine‐induced hyperactivity and dopamine transporter trafficking to the plasma membrane

Abstract: As well known, cocaine induces stimulant effects and dopamine transporter (DAT) trafficking to the plasma membrane of dopaminergic neurons. In the present study, we examined cocaine‐induced hyperactivity along with cocaine‐induced DAT trafficking and the recovery rate of the dopaminergic system in female rats in comparison with male rats, demonstrating interesting gender differences. Female rats are initially more sensitive to cocaine than male rats in terms of both the DAT trafficking and hyperactivity induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…in rats) 61 . It was also demonstrated that CocH5-Fc(M6) effectively blocked cocaine-induced dopamine transporter (DAT) trafficking (associated with cocaine dependence) with repeated cocaine exposures by maintaining a plasma CocH5-Fc(M6) concentration ≥ 58.7 ± 2.9 nM in rats 62 , 63 . Through protecting the dopaminergic system and allowing the system to recover from cocaine-induced DAT trafficking, CocH5-Fc(M6) has become a promising therapeutic candidate, suitable for treatment of cocaine dependence 60 , 62 64 .…”
Section: Introductionmentioning
confidence: 99%
“…in rats) 61 . It was also demonstrated that CocH5-Fc(M6) effectively blocked cocaine-induced dopamine transporter (DAT) trafficking (associated with cocaine dependence) with repeated cocaine exposures by maintaining a plasma CocH5-Fc(M6) concentration ≥ 58.7 ± 2.9 nM in rats 62 , 63 . Through protecting the dopaminergic system and allowing the system to recover from cocaine-induced DAT trafficking, CocH5-Fc(M6) has become a promising therapeutic candidate, suitable for treatment of cocaine dependence 60 , 62 64 .…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Unfortunately, cocaine interacts with many human proteins, including multiple receptors and transporters in the brain. 3,[6][7][8][9][10][11] It would be extremely challenging to directly antagonize the physiological effects of cocaine without impairing the brain's normal functions because all the neuronal receptors and transporters have their own normal physiological functions. Hence, there is still no FDA-approved pharmacotherapy specific for cocaine addiction or overdose.…”
Section: Introductionmentioning
confidence: 99%
“…Several preclinical studies have explored DAT quantity and function following psychostimulant administration (reviewed in [ 125 ]). Deng et al showed that in response to cocaine administration, female mice showed augmented DAT trafficking to the membrane when compared to male mice [ 126 ]. With repeated cocaine self-administration in rats, researchers have observed, in ex vivo slice preparations, reduced rates of DA uptake in striatal areas, a reduced potency of cocaine to block DAT after local infusion, and a priming towards reinstatement even after 60 days of abstinence [ 127 , 128 , 129 , 130 , 131 ].…”
Section: Introductionmentioning
confidence: 99%